Corporate Criminal Responsibility for Corruption Crimes in Perspective Perma No. 13 of 2016 - Hermawan; Akhmad Taufiq; Setyo Nugroho Haribowo (Universitas Muhammadiyah Palu, 2021)
Corporations as perpetrators of criminal acts can be criminally charged, because corporations are legal subjects and therefore can be held criminally responsible. PERMA Number 13 of 2016 dated December 21 2016 concerning Procedures for Handling Criminal Cases by Corporations, regulates matters namely corporate and management criminal liability, corporate group accountability, corporate responsibility in mergers, consolidations, separations and dissolution of corporations, corporate audit procedures, procedures for examining management, procedures for examining corporations and management, claims for compensation and restitution, handling of corporate assets, abolition of the authority to prosecute and carry out crimes, sentencing, criminal decisions, implementation of decisions and implementation of additional crimes or regulations against corporations.